(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2016)
Broad ligament pregnancy is an extremely rare event with high risk of maternal mortality. Diagnosis is often late in our setting and finally made during laparotomy. It is a type of secondary abdominal pregnancy.We present a case which remained undiagnosed throughout her pregnancy till she reached to 35 weeks and unfortunately had intrauterine fetal demise when she reported to our hospital.After admission her pregnancy was induced with misoprostol but did not response. On clinical suspicion,repeat ultrasound evaluation was done by senior sinologist, which picked up the diagnosis of abdominal pregnancy. On laparotomy a broad ligament pregnancy was found with a rent in the previous Cesarean scar towards the gestational sac in the broad ligament. Chatt Shi Hosp Med Coll J; Vol.15 (1); Jan 2016; Page 60-62